2008
DOI: 10.1007/s11999-008-0388-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Silicone Sheets on Microvascular Anastomosis

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In such a case, a sterile silicone sheet is placed between the flap and the abdominal muscle. The sheet is sutured to the edges of a flap to prevent its movement, which may cause a physical damage to the pedicle [ 147 ]. Although some wound bed isolation studies conducted on single animals showed a significant reduction of flap survival rates [ 148 , 149 ], other investigators did not see a significant difference in functional flap outcome, but agreed that induction of potent pro-inflammatory response by a foreign material might conceal the true driving forces of the healing process [ 150 ].…”
Section: Discussionmentioning
confidence: 99%
“…In such a case, a sterile silicone sheet is placed between the flap and the abdominal muscle. The sheet is sutured to the edges of a flap to prevent its movement, which may cause a physical damage to the pedicle [ 147 ]. Although some wound bed isolation studies conducted on single animals showed a significant reduction of flap survival rates [ 148 , 149 ], other investigators did not see a significant difference in functional flap outcome, but agreed that induction of potent pro-inflammatory response by a foreign material might conceal the true driving forces of the healing process [ 150 ].…”
Section: Discussionmentioning
confidence: 99%